Enhancement of user experience and accessibility for Twittener web application - Ng, Hong Quan (2017)
As the number of global internet users grows, so does the number of people who are using social media to stay connected. Twitter is a popular social networking and microblogging service used by hundreds of million globally. It allows users to get the latest information in a quick and concise way and to keep up with online trends and topics. Twittener, an alternative way to interact with Twitter was developed by a previous student for his final year project. The project aims to promote inclusiveness by improving the accessibility of Twitter for people with physical disabilities, visual impairments and the elderly to join in social conversations and to keep up to date with happenings around the world. The Twittener system whose name is a combination of the words “Twitter” and “Listen” comprises of two application. The web application allows users to listen to interesting tweets instead of the conventional way of reading them. While a console application periodically crawls feeds of Twitter accounts in pre-defined topics to retrieve the latest updates from these accounts. Text-to-speech technology and sentiment analysis are employed to convert tweets with high sentiment value to audio which are served to the users. Continuing on from the work done by the previous student for his final year project, this project seeks to make improvements to the web application to further enhance user experience and accessibility. The user interface was revamped and additional functionalities were added. Some of these functionalities include customization of topics and speech input for site navigation and posting of tweets. This report serves to document the system analysis, design, and implementation of the improvements to the Twittener web application.